Recent advances in elastomeric nanocomposites - Mittal, Vikas (Advanced Structured Materials, 2011)
"Recent Advances in Elastomeric Nanocomposites" reviews the recent progresses in the synthesis, processing as well as applications of elastomeric nanocomposites. Elastomers are a very important class of polymer materials and the generation of their nanocomposites by the incorporation of nano-filler has led to significant enhancement of their properties and, hence, expansion of their application potential. Most of the studies related with these materials are present in the form of research papers. Here, the authors present a comprehensive text covering the whole of the subject. The book is tailored more from the applications point of view, but also provide enough introductory material for research scholars new to this field.